2008
DOI: 10.1121/1.2935781
|View full text |Cite
|
Sign up to set email alerts
|

Identifying speaker-dependent acoustic parameters in Spanish vowels

Abstract: Speaker-dependent parameters (F3-F4) are expected to show a lower SD when grouped by speaker/session, Vowel quality parameters (F1-F2) are supposed to have a lower SD when grouped by phoneme. F0 would be related both to the speaker and the vowel quality. Results show that F2 is the parameter with the highest SD. F4 the one with lowest SD. F0 is highly variable between vowels. No significant differentes are found in any of the parameters when grouping by session or by speaker. Speaker/session clustering (all vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Studies have shown that both F3 and F4 are important to speaker recognition [4] and that strengthening the presence of higher formants can improve the robustness of cross-session speaker recognition [4].…”
Section: Chart 1: Impact Of Vtl and Pitch Rescaling On Speaker Recognmentioning
confidence: 99%
“…Studies have shown that both F3 and F4 are important to speaker recognition [4] and that strengthening the presence of higher formants can improve the robustness of cross-session speaker recognition [4].…”
Section: Chart 1: Impact Of Vtl and Pitch Rescaling On Speaker Recognmentioning
confidence: 99%
“…A preliminary result, using the vowels in each recording, is obtained, and due to the great amount working, 17 speaker is using to evaluate the vowels, the vowel /a/, present the best performance, the vowels /u/ has been exclude because of its low frequency of occurrence in Spanish [14], [15], and the vowels /i/, is exclude, because has less in comparison with the others vowels, but in a future work will be used.…”
Section: Discussionmentioning
confidence: 99%